Control of Sexual Transmitted Infections in Indonesia - Festy Mahanani Mulyaningrum; Aris Sudiyanto; Sapja Anantanyu; Argyo Demartoto; Ade Saputra Nasution (Indian Journal of Forensic Medicine & Toxicology, 2021)
Female indirect commercial sex workers who usually work in certain fields of work or have other main jobs and indirectly sell sex in entertainment places such as masseuses, bar waiters. They are included in the high risk group in the spread of cases of Sexual Transmitted Infections and HIV and AIDS. In Indonesia, it is hoped that HIV AIDS will be free from Sexual Transmitted Infection by 2030 with the vision and mission “No more HIV transmission, no AIDS deaths, no more stigma and discrimination in people with HIV / AIDS”. This type of research uses quantitative descriptive research. with a sample of 80 female sex workers in Bandungan, Semarang. The results of this study indicate a significant relationship between customer support, access to health services, health promotion and control of sexually transmitted infections.